Riziko dopadu internetových sociálních sítí na životní styl studentů - Homolková, Vendula; Taliánová, Magda (Univerzita Pardubice, 2012)
The report is focused on the isme of usage of social networks in everyday life of students and possible impal of these activities on their psychosomatic state. The research was performed at 200 students of secondary and high school, aimed at the students with healthcare focus, agend from 15 to 24 years. The studied area was the whole Eastern Bohemian region. The results of surfy based research were processed by relative frequency and two-sample t-test with aquel variance.
The risk of impact on line social networks on students lifestyle
Keywords: social network; school; relationships; way of living